Comparison of two variants of a kata technique (Unsu): The neuromechanical point of view - Camomilla, V.; Sbriccoli, P.; Di Mario, A.; Arpante, A.; Felici, F. (Journal of Sports Science & Medicine, 2009)
The objective of this work was to characterize from a neuromechanical point of view a jump performed within the sequence of Kata Unsu in International top level karateka. A modified jumping technique was proposed to improve the already acquired technique. The neuromechanical evaluation, paralleled by a refereeing judgment, was then used to compare modified and classic technique to test if the modification could lead to a better performance capacity, e.g. a higher score during an official competition. To this purpose, four high ranked karateka were recruited and instructed to perform the two jumps. Surface electromyographic signals were recorded in a bipolar mode from the vastus lateralis, rectus femoris, biceps femoris, gluteus maximus, and gastrocnemious muscles of both lower limbs. Mechanical data were collected by means of a stereophotogrammetric system and force platforms. Performance was associated to parameters characterizing the initial conditions of the aerial phase and to the CoM maximal height. The most critical elements having a negative influence on the arbitral evaluation were associated to quantitative error indicators. 3D reconstruction of the movement and videos were used to obtain the referee scores. The Unsu jump was divided into five phases (preparation, take off, ascending flight, descending flight, and landing) and the critical elements were highlighted. When comparing the techniques, no difference was found in the pattern of sEMG activation of the throwing leg muscles, while the push leg showed an earlier activation of RF and GA muscles at the beginning of the modified technique. The only significant improvement associated with the modified technique was evidenced at the beginning of the aerial phase, while there was no significant improvement of the referee score. Nevertheless, the proposed neuromechanical analysis, finalized to correlate technique features with the core performance indicators, is new in the field and is a promising tool to perform further analyses.